Pengaruh Penjualan Online Melalui Media Sosial Whatsapp Terhadap Loyalitas Pembeli di UMKM - Dini Aminarti; Winna Sarikusumaningtyas, Boma Jonaldy Tanjung (YUME : Journal of Management, 2025)
The advancement of digital technology has transformed buying and selling patterns, including in the vegetable trading sector. Social media, particularly WhatsApp, now serves not only as a communication tool but also as an effective marketing platform for micro-entrepreneurs. This study aims to examine the influence of online vegetable sales through WhatsApp on customer loyalty.This research adopts a quantitative approach using a survey method. Respondents were selected through purposive sampling, involving 100 active consumers who regularly purchase vegetables online via WhatsApp. Data were collected using an online questionnaire and analyzed using simple linear regression with the help of SPSS version 27.The findings reveal that online vegetable sales through WhatsApp have a positive and significant effect on customer loyalty. This is indicated by a significance value below 0.05 and a fairly strong coefficient of determination. The results suggest that ease of access, personalized communication via WhatsApp contribute to building long-term relationships between sellers and buyers.This research offers practical insights for vegetable sellers to optimize WhatsApp as a marketing channel and a means of fostering customer loyalty. Moreover, it contributes to the growing literature on digital marketing strategies in the context of micro and small enterprises during the digital transformation era. Keywords: Online Sales, WhatsApp, Customer Loyalty, Social Media, Digital Marketing.